KERAJAAN SAFAWI DI PERSIA DAN MUGHAL DI INDIA ASAL USUL, KEMAJUAN DAN KEHANCURAN - Desky, Harjoni (Tasamuh: Jurnal Studi Islam, 2016)
Before becoming a great empire, the Safavid empire is just a movement of the congregation founded by Safi al-Din al-Ardabily Isaac (1252-1334 AD) in Ardabil, Azerbijan. The congregation is called Safavid taken from the name of its founder. The name survived until the movement is turning into a political movement, even to successfully establish the kingdom. Safi al-Din is a Shiite Sufi wing. Some historians say that he was a descendant of the seventh Shiite imam Ithna âAsyariah, Musa al-Qasim. While the origin of the establishment of the Mughal empire in India, through such a long process. Historical background, it can be seen after the fragility of the Delhi Sultanate (1192-1525 AD), precisely in the period Khalji and Tughluq, followed by family Sayyid (1414-1451 AD), as well as family Lodi (1451-1512 AD). At that time, the condition of Muslim rule in India suffered a setback and showed a very complicated thing, namely the rise of the old mind who believe that every independent kingdom was caliph in the middle of their own environment. This article speaks of the two Islamic kingdoms.